Inhibition Effect of Some Plant Extracts on The Corrosion of Mild Steel in H2SO4 Medium - Dakmouche, M.; Ladjel, S.; Gherraf, N.; Saidi, M.; Hadjaj, M.; R. Ouahrani, M. (Asian Journal of Chemistry, 2010)
The inhibitive effect of extracts of Cotula cinerae, Retama retam and Artemisia herba alba plants on the corrosion of X52 mild steel in aqueous 20 % (2.3 M) sulfuric acid was investigated. Weight-loss determinations and electrochemical measurements were performed. Polarization curves indicated that the plant extracts behave as mixed-type inhibitors. The corrosion rates of steel and the inhibition efficiencies of the extracts were calculated. The results reveal that the extract solutions of the plants could serve as effective inhibitors for the corrosion of steel in sulphuric acid media. Inhibition rate was found to increase with increasing concentration of the plants extract up to an optimum concentration.